Two-Stage Email Classification Model for Enhanced Spam Filtering Through Feature Transformation and Iterative Learning - Stow, May; Ezonfa, Bolou-ebi Samuel (International Journal of Computer Sciences and Engineering, 2025)
Email spam remains a persistent challenge, with cybercriminals constantly evolving tactics to bypass traditional detection methods. In response, this research introduces a novel two-stage classification model that combines the strengths of logistic regression, principal component analysis (PCA), and a feedforward neural network to achieve exceptional spam detection performance. The first stage employs a rapid logistic regression classifier to filter out obvious spam emails, dramatically reducing computational overhead. We then subject the remaining emails to Principal Component Analysis (PCA), extracting the most salient features while minimizing noise and dimensionality. This transformed feature space is then fed into a neural network, empowering it to capture the complex, non-linear patterns indicative of sophisticated spam attacks. Evaluation of the widely-used SpamAssassin Public Corpus and Lingspam datasets demonstrated the synergistic benefits of this hybrid approach, achieving 98.0% accuracy in spam detection for the Spam Assassin Public Corpus, which was refined from an initial accuracy of 99.95% following further testing and optimization, and 99.34% accuracy for the Lingspam dataset respectively, in spam detection. The strategic combination of techniques transcends the traditional speed-accuracy tradeoff, simultaneously creating a new benchmark in both performance metrics. This robustness, consistency, and scalability make the proposed model a practical and effective solution for real-world spam filtering, with significant implications for securing email communication and protecting users from cybercrime.